Ban on female migrant workers: Skills-differentiated evidence from Sri Lanka - Bilesha Weeraratne (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
This study examines the skills-differentiated impact of a restrictive female labour migration policy in Sri Lanka using monthly departure data from 2012 to 2018 in a difference-indifference model. The Family Background Report policy has resulted in decreasing departures among lower-skilled groups-female domestic, unskilled, semi-skilled, and skilled workers-and increasing departures among middle-level and professional workers. The decrease in departures of lower-skilled groups is consistent with the objectives of the policy and existing impact evaluation studies, while the increase in higher-skilled workers is consistent with the literature on Family Background Report-related corruption and mis-reporting of skills to avoid the policy. Thus, the policy is associated with higher involvement of lower-skilled workers in recruitment-related corruption, higher exposure to recruitment-related vulnerability, and lower foreign employment opportunities. The study also finds that it was appropriate to exempt the 45-49 year age group from the Family Background Report requirement in 2017.
Keywords: J16; J22; J24; J61; 330; labour migration; employment; female; difference-in-difference; skills